The potential impact of hereditary hemochromatosis on the heart considering the disease stage and patient age—the role of echocardiography - Świątczak, Michał; Rozwadowska, Katarzyna; Sikorska, Katarzyna; Młodziński, Krzysztof; Świątczak, Agata; Raczak, Grzegorz; Daniłowicz-Szymanowicz, Ludmiła (Frontiers in Cardiovascular Medicine, 2023)
Background. Hereditary hemochromatosis (HH) is a genetic disease that leads to increased iron accumulation in several organs. Cardiomyocytes are highly susceptible to this damage owing to their high iron uptake, and cardiovascular complications account for 1/3 of the deaths in the natural course of HH. Additionally, excess iron intake and associated oxidative stress may accelerate the aging of the cardiovascular system, regardless of the age of patients with HH. We aimed to investigate the role of standard and speckle-tracking echocardiography (STE) in revealing heart differences in patients with HH considering the disease stage and the patient age. Methodology. Consecutive patients with HH (n = 58) without heart pathologies (except hypertension) and 29 age- and sex-matched healthy individuals underwent echocardiography. Patients were compared according to the time since HH diagnosis (the recently diagnosed HH group [31 patients] with diagnosed HH for less than six months and had no more than one venesection; the medium group [11 patients] with diagnosed HH between six and twenty-four months; and the long-lasting group [16 patients] with diagnosed HH for more than two years) and the quartile contribution of their age. Results. Standard echocardiography revealed differences in diastolic parameters between patients with HH and controls, which were the most prominent between healthy and long-lasting HH patients. Regarding systolic function, left ventricular ejection fraction was lower in HH patients, with the most evident differences between the healthy and recently diagnosed HH patients. STE revealed additional differences in systolic parameters, with LV rotation the worst in recently diagnosed patients and its increase in patients with medium and long-lasting HH. Significantly worse peak systolic longitudinal strain values were observed in all patients with HH. Analyses of the results according to age quartiles of patients with HH revealed that some changes ocurred earlier than expected according to age. Conclusions. Echocardiography can reveal the possible heart damage in HH patients at different stages of the disease and highlight potential features of accelerated myocardial aging in these patients.